2018
DOI: 10.1007/s00431-018-3098-x
|View full text |Cite|
|
Sign up to set email alerts
|

Hyperpyrexia and high fever as a predictor for serious bacterial infection (SBI) in children—a systematic review

Abstract: Young infants with temperature higher than 400 °C are at increased risk for SBI. Risk of SBI in older children with temperature > 400C is minimal. What is known: • An association between high fever and increased risk for SBI was reported in young infants. • Based on only two studies from the 1970s and 1980s, hyperpyrexia is associated with increased risk for SBI. What is new: • Infants under the age of 3 months with fever > 40 °C were found to have increased risk for SBI. • Risk of SBI in older children with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
1
21
2
Order By: Relevance
“…It is well known that the incidence of pneumonia decreases with the introduction of the pneumococcal vaccine in the routine vaccination schedule [20] . The clinical and lab predictors of SBI identified in this study are similar to those previously reported [21][22][23][24] . In this study, pyuria as a simple point-of-care test had high specificity for predicting UTI, and 50% of UTIs were due to ESBL producing organisms.…”
Section: Discussionsupporting
confidence: 88%
“…It is well known that the incidence of pneumonia decreases with the introduction of the pneumococcal vaccine in the routine vaccination schedule [20] . The clinical and lab predictors of SBI identified in this study are similar to those previously reported [21][22][23][24] . In this study, pyuria as a simple point-of-care test had high specificity for predicting UTI, and 50% of UTIs were due to ESBL producing organisms.…”
Section: Discussionsupporting
confidence: 88%
“…This kind of fever does not require any long-term treatment and disappears on its own without any sequelae. Hyperpyrexia, indicative of bacterial infection, can also be diagnosed quickly by checking the patient’s medical history, physical examination and basic laboratory tests 3–5. However, some children suffer from long-term fevers with temperature higher than 38.3°C that last for months or even years without any clear diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have investigated predictors of SBI in young infants by implementing criteria or developing prediction models, few studies have focused on using the vital signs, such as body temperature, pulse rate, and oxygen saturation . One subgroup analysis of a systematic review showed that young infants with fever >40°C had a significantly high risk of SBI, but no study has defined the cut‐off point for each vital sign. The concept of systemic inflammatory response syndrome (SIRS) may be useful in this regard because SIRS is defined according to vital sign cut‐offs .…”
Section: Discussionmentioning
confidence: 99%